2021
DOI: 10.3390/en14072014
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Power Frequency Converter and Application in High-Voltage and Partial Discharge Test of a Voltage Transformer

Abstract: This paper presents application of a resonant power frequency converter for high-voltage (HV) and partial discharge (PD) test of a voltage transformer. The rating voltage, power, and frequency of the system are 70 kVrms, 40 kVA, and 200 Hz, respectively. The testing system utilized the converter feeding to an HV testing transformer connected to a conventional partial discharge detection system. The converter system comprising a rectifier and insulated-gate bipolar (IGBT) switches with the H-bridge configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In equation ( 3), ( ') yn to consider the pre emphasis audio signal of time domain signal; () xm is the audio signal sampling value at time m; w is the window function bandwidth. In this paper, the bandwidth of the window function is leaked, and the bandwidth of the signal main lobe is widened to ensure the high frequency division [25] of spectrum analysis. The window function expression is as follows:…”
Section: Processing Partial Discharge Noise Signal Of Ring Main Unit ...mentioning
confidence: 99%
“…In equation ( 3), ( ') yn to consider the pre emphasis audio signal of time domain signal; () xm is the audio signal sampling value at time m; w is the window function bandwidth. In this paper, the bandwidth of the window function is leaked, and the bandwidth of the signal main lobe is widened to ensure the high frequency division [25] of spectrum analysis. The window function expression is as follows:…”
Section: Processing Partial Discharge Noise Signal Of Ring Main Unit ...mentioning
confidence: 99%
“…For example, in [1][2][3] the electronic converter dynamic properties were analyzed in a specific usage but there is no analysis of the influence of the parameters on the converter work dynamic. In [4][5][6][7][8] a DC voltage rectifier with a triple band was proposed. In comparison with other similar constructions, it is highly efficient and compact.…”
Section: Analysis Of Publicationsmentioning
confidence: 99%
“…However, some parameters cannot be measured accurately in real practice. In the design process of [14], the parameters in the simulation were adjusted to obtain results that were consistent with the experimental ones. It would be advantageous for the system design if the circuit parameters could be determined accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there have been attempts to develop the HV and PD tests of HV equipment. In [6][7][8][9], a power frequency converter based on pulse-width modulation (PWM) techniques was developed as a low-voltage source for the HV testing transformer for the HV and PD tests. It was found that the commercial and self-developed frequency converters with a voltage filter can generate an almost-pure sinusoidal voltage waveform, but the PWM switching generates a high noise level, which is higher than the acceptable level (2.5 pC) of the PD test.…”
Section: Introductionmentioning
confidence: 99%